Upaya pencegahan stunting dengan pemanfaatan herbal Indonesia di TK model Terpadu Bojonegoro - Ria indah Kusuma Pitaloka (CV. Agrapana Media, 2026)
Stunting is a chronic nutritional problem that has long-term impacts on physical growth, cognitive development, and the quality of human resources. Efforts to prevent stunting need to be carried out from an early age through educational, participatory approaches based on local potential. This community service activity aims to support stunting prevention through the utilization of Indonesian herbal resources at TK Model Terpadu Bojonegoro. The methods employed include socialization and education on stunting and child nutrition, training and practical sessions on the safe and beneficial use of herbal products, as well as mentoring and implementation within learning activities and healthy lifestyle habits. The target participants are teachers and parents, who play a central role in shaping children’s healthy behaviors. The results of the program indicate an increase in knowledge, positive changes in attitudes, and improved skills among the target community in utilizing local herbal resources to support children’s health. In addition, the activity strengthens the role of early childhood education institutions as agents of change in stunting prevention. The impact of the community service is evident both in the short term through increased awareness and community participation and in the long term, through the potential establishment of a healthy lifestyle culture based on local wisdom and improved family economic efficiency. Thus, this community service initiative provides added value in social, cultural, and economic aspects, and has the potential to become a sustainable and replicable model for community engagement in other regions.